2022
DOI: 10.1186/s13063-021-05848-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of iodine complex in SARS-CoV-2-infected patients with mild to moderate symptoms: study protocol for a randomized controlled trial

Abstract: Background Coronavirus disease 2019 (COVID-19) caused by the novel coronavirus-infected millions globally. Despite a wide range of advised options for the treatment of COVID-19, a single strategy to tackle this pandemic remains elusive, thus far. That is why we are conducting a clinical trial to find out the efficacy of iodine complex to clear a viral load of severe respiratory syndrome coronavirus-2 (SARS-CoV-2) along with a reduction in time taken to alleviate symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Based on these findings, it was concluded that Renessans has an in vivo SARS-CoV-2 activity and may result in early clearance of the virus, that provides a basis for the clinical trial of the drug in SARS-CoV-2 patients and reveal its anti-SARS-CoV-2 potential [100]. As per the latest update, a controlled randomized ongoing trial is being conducted to evaluate the effectiveness of this iodine complex for clinical and radiological improvements in patients affected with mild to moderate COVID-19 in Pakistan [100,101].…”
Section: Renessansmentioning
confidence: 99%
“…Based on these findings, it was concluded that Renessans has an in vivo SARS-CoV-2 activity and may result in early clearance of the virus, that provides a basis for the clinical trial of the drug in SARS-CoV-2 patients and reveal its anti-SARS-CoV-2 potential [100]. As per the latest update, a controlled randomized ongoing trial is being conducted to evaluate the effectiveness of this iodine complex for clinical and radiological improvements in patients affected with mild to moderate COVID-19 in Pakistan [100,101].…”
Section: Renessansmentioning
confidence: 99%